Falsche Interpretation einer neuen CBD-Studie (Zeitschrift für Phytotherapie, 2024)
Pramhas S, Thalhammer T, Terner S et al. Oral cannabidiol (CBD) as add-on to paracetamol for painful chronic osteoarthritis of the knee: a randomized, double-blind, placebo-controlled clinical trial. Lancet 2023; 35: 100777. DOI: 10.1016/j.lanepe.2023.100777